Pelatihan Smart Multi-Culture Farming Berbasis Teknologi Cloud-AI untuk Pemantauan Objek Budidaya dengan Tenaga Surya sebagai Eco-Green Energy Masyarakat Indonesia - Santoso, Nurudin; Cholissodin, Imam; Soebroto, Arief Andy; Hidayat, Nurul; Sutrisno, Sutrisno; Pratiwi, Destyana Ellingga; Fathuroya, Vivien (JAST : Jurnal Aplikasi Sains dan Teknologi, 2022)
Working in multicultural agriculture is exhausting and has several bad risks for farmers in rural and urban areas. The risks start from the considerable time required in cultivation, especially when maintaining the growth and development of plants and other cultivation objects, the large number of costs required in the use of irrigation for fuel purchases, and the risk of carrying out specific processes using high voltage electricity which is very dangerous for farmers. Based on these problems, an automated technology approach that can work to help farmers is necessitated. In this community service, two partners are involved, i.e., a group of farmers who are also workers in Kampung Kauman RW/RT III/03 as the primary partner and a group of farmers who are also workers at the plantation in Poncokusumo Malang as the supporting partner. Both partners used solar electricity for irrigation and other uses through the Cloud-AI approach obtained from the results of multi-disciplinary research several years earlier at the Filkom UB Intelligent Computing Laboratory. Cloud-AI can work adaptively according to weather conditions from a Web App from application programming interface (API) data to provide recommendations for predicting the length of time for irrigation in observing cultivation objects which later can be modified for other particular purposes. The activity's primary results are providing training and assistance with intelligent multi-culture farming installation tools for hydroponics, solar panels, and pumps for irrigation: cloud-AI-based agricultural training modules and educational videos with excellent responses from the partners.ABSTRAKProses pengerjaan bidang pertanian multi-culture sangat menguras banyak tenaga dan memiliki beberapa resiko kurang baik bagi petani, baik di pedesaan maupun perkotaan. Mulai dari waktu yang cukup banyak dibutuhkan dalam pembudidayaan terutama saat pemeliharaan tumbuh kembangnya tanaman maupun objek budidaya lainnya, lalu banyaknya biaya yang dibutuhkan dalam penggunaan irigasi untuk pembelian bahan bakar serta resiko ketika melakukan proses tertentu menggunakan listrik tegangan tinggi yang sangat membahayakan petani. Berdasarkan permasalahan tersebut dibutuhkan pendekatan teknologi otomasi yang dapat bekerja membantu petani. Dalam pengabdian ini melibatkan Dua Mitra, yaitu di kelompok petani yang sekaligus pekerja Kampung Kauman RW/RT III/03 dan pada Perkebunan di Poncokusumo Malang yang memanfaatkan listrik tenaga surya untuk irigasi dan kegunaan lainnya serta pendekatan Cloud-AI yang dapat bekerja secara adaptif baik luring maupun daring untuk mengendalikan kelistrikan, prediksi untuk pengambilan keputusan dalam pengamatan objek budidaya dan lainnya. Hasil utama kegiatan berupa pemberian pelatihan, lalu bantuan paket alat instalasi smart multi-culture farming untuk hidroponik, panel surya dan pompa untuk irigasi serta modul pelatihan pertanian berbasis Cloud-AI dan video edukasi dengan respon yang sangat baik dari Mitra.